2016
DOI: 10.3390/en9020117
|View full text |Cite
|
Sign up to set email alerts
|

Performance Analysis of a Grid-connected High Concentrating Photovoltaic System under Practical Operation Conditions

Abstract: High concentrating photovoltaic (HCPV) is a promising technique for the practical commercial utilization of solar energy. However, the performance of a HCPV system is significantly influenced by environmental parameters such as solar direct normal irradiance (DNI) level and environmental temperature. This paper analyzes the performance of a 9 kW p grid-connected HCPV system in Kunming (Yunnan, China), during practical field operations over an entire year, and discusses how the environmental parameters influenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 25 publications
(20 reference statements)
0
2
0
Order By: Relevance
“…The average wind speed in Kunmig during the autumn season is 1.94 m/s (www.weatherspark.com), and the present results showed that the power consumed by the tracker was 3.608 W, which represents a 0.5% deviation from the experimental data. Furthermore, the present results of power consumed by the tracker were also compared with the one-year experimental results from the practical field operation of the 9 kW HCPV FIGURE 5 Top view of optimal heat spreader of photovoltaic module segment system constructed in Kunming, China [43]. Their system consisted of 96 modules, and each had 24 solar cells.…”
Section: Validation Of Consumed Power Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The average wind speed in Kunmig during the autumn season is 1.94 m/s (www.weatherspark.com), and the present results showed that the power consumed by the tracker was 3.608 W, which represents a 0.5% deviation from the experimental data. Furthermore, the present results of power consumed by the tracker were also compared with the one-year experimental results from the practical field operation of the 9 kW HCPV FIGURE 5 Top view of optimal heat spreader of photovoltaic module segment system constructed in Kunming, China [43]. Their system consisted of 96 modules, and each had 24 solar cells.…”
Section: Validation Of Consumed Power Resultsmentioning
confidence: 99%
“…Furthermore, the present results of power consumed by the tracker were also compared with the one‐year experimental results from the practical field operation of the 9 kW HCPV system constructed in Kunming, China [43]. Their system consisted of 96 modules, and each had 24 solar cells.…”
Section: Validation Of the Analytical Solutionmentioning
confidence: 99%